KAKA INCENSE'S STRUGGLE AGAINST THE NETHERLANDS IN THE KINGDOM OF NANGAPANDA 1892-1907 - Damianus Rikardo Sumbi Wasa; Aloysius Wasa; Nong Hoban (Sean Institute, 2022)
The world has become a field of life successively, era after age has passed, generation after generation has disappeared as the saying goes that everything that dies will leave something precious to the generation in front of it. This fact is represented in a meaningful historical story. Consciously or unconsciously, what our predecessors pioneered is a motivation for us to move forward in overcoming various problems or problems of the nation. We as citizens of course know and know the history of the nation and country properly and correctly. Through history allows us to know the past of our nation and country. By knowing the past, we can take lessons from these events to draw conclusions. Badrika (1994:4) states that history contains three meanings as follows: (1) history as genealogy or origin (2) history means events or events that actually happened in the past, (3) history means science, stories lessons about the past. Kartodirjo (1992: 287) put forward his main argument that in essence history provides a picture for humans in observing and changing the world in the present and the future. Based on observations on historical events in the past, people will recognize, appreciate and understand the rules that can be used as material for thinking and acting to advance human life and the universe in the present and even for the future.